Determinant Factor of Pulmonary Function Impairment on Rice Mill Workers - Hernanda Arie Nurfitria; Retno Adriyani; Shulkhiatus Syafa'ah (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: Exposure to organic dust in the agricultural industry can cause pulmonary function problems for workers. This study aims to know the determinant of pulmonary function impairment on rice mill workers in Ujung Pangkah, Gresik, East Java. Method: This study was an analytical observational study using a cross-sectional design. This study's population were all rice mill workers in Ketapang and Glatik Villages, Ujung Pangkah, Gresik, East Java there were 25 people. The sample of this study was 16 people. The independent variable in this study was the sex, working period, smoking, and using a mask, while the dependent variable was the pulmonary function status of workers. The data respondent obtained a questionnaire, observations, and measurement of workers' pulmonary function using a spirometer. Data analysis was performed in analytic descriptive with the Spearman correlation test. Result and Discussion: The Spearman test results are known that the working period (r = -0.022) and smoking (r = -0.160) were very weak and an inverse correlation with pulmonary function status. In comparison, the use of masks (r = 0.462) was adequate and directly correlated with pulmonary function status. Smoking and working period will describe the length of exposure to rice dust, affecting the pulmonary function status. The obedience of using masks to workers will reduce the risk of pulmonary function impairment. Conclusion: Working period, smoking, and using mask are determinants of pulmonary function impairment on rice mill workers in Ujung Pangkah, Gresik, East Java.